NK cell-macrophage interactions in granulomas correlate with limited tuberculosis pathology - Niewold, Paula; IJsselsteijn, Marieke E.; Dijkman, Karin; de Miranda, Noel; Ottenhoff, Tom H. M.; Verreck, Frank A. W.; Joosten, Simone A. (PLoS pathogens, 2025)
Development of novel vaccines and treatment approaches against tuberculosis are hampered by limited knowledge of what constitutes a protective immune response against Mycobacterium tuberculosis ( Mtb ). Granulomas are organized immune aggregates that form in the lung in response to mycobacterial infection and are an important site of pathogen-host interaction. The composition and cellular microenvironment within the granuloma impacts the bacterial control capacity. To identify protective responses in granulomas, imaging mass cytometry was used to study archived lung tissue from low dose Mtb -infected non-human primates presenting with various levels of disease. This approach revealed that granuloma composition is correlated with the severity of lung pathology. Granulomas of animals with limited lung pathology were enriched for NK cells showing increased interactions with tissue macrophages. This work improves our understanding of local immune interactions in the lung and how these correlate with severity of tuberculosis disease.